Independent impact of periodontitis and cardiovascular disease on elevated soluble urokinase‐type plasminogen activator receptor (suPAR) levels. Issue 6 (6th November 2020) - Isola, Gaetano; Polizzi, Alessandro; Alibrandi, Angela; Williams, Ray C.; Leonardi, Rosalia
Abstract: Background: Previous studies have demonstrated that a soluble urokinase‐type plasminogen activator receptor (suPAR) plays an essential function in leukocytes and endothelial homeostasis and, therefore, in the development of coronary heart disease (CHD) and periodontitis. The aim of this study was to analyze the impact of gingival health, periodontitis, and CHD on suPAR levels in plasma and saliva and to evaluate suPAR as a biomarker of periodontitis and CHD. Methods: Healthy controls (n = 33), patients with periodontitis (n = 31), CHD (n = 29), and a combination of periodontitis + CHD (n = 29) were enrolled in the present study. All patients were clinically and periodontally evaluated and regularly assessed for socioeconomic status, serum lipids, high‐sensitivity C‐reactive protein (hs‐CRP), and for plasma and salivary suPAR levels. Results: Patients with periodontitis ( P  <.001) and with periodontitis + CHD ( P  <.001) presented higher median plasma and salivary suPAR levels compared with CHD and healthy controls. Moreover, univariate regression analysis demonstrated that hs‐CRP ( P  <.001) and periodontitis ( P  <.001) had a significant negative direct effect on both plasma and salivary suPAR levels. The multivariate regression analysis showed that periodontitis was the only significant predictor of plasma suPAR ( P  = .035) while hs‐CRP was the only significant predictor of salivary suPAR ( P  <.001). Conclusions: The results of the present study demonstrated that patients with periodontitis and periodontitis + CHD presented higher suPAR levels in both plasma and saliva in comparison with healthy controls and CHD. Moreover, periodontitis and hs‐CRP were the only significant predictors of the augmented suPAR levels in plasma and saliva, respectively.